2021
DOI: 10.1016/j.transci.2020.103017
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma therapy in patients with COVID-19

Abstract: We would like to express our sincere thanks to the author's interest in our paper, and we are also grateful for her adding invaluable contribution to improve the value of our paper. Unfortunately, during the current pandemic, more than 1 million people died because of COVID-19, and millions of people needed hospitalization, and some needed intensive care unit (ICU) support. Until the active vaccination against SARS-CoV-2 reaches large populations, effective treatments and supportive approaches are crucial to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 5 publications
2
45
0
2
Order By: Relevance
“…The literature search yielded 171 studies, of which 38 studies met the eligibility criteria. The present analyses included a total of eighteen clinical trials including five RCTs, 7,8,12,13,15 thirteen matched-control studies, 11,16,2527,1724 and twenty case series or case reports 10,28,37–46,2936 containing 10,436 COVID-19 patient outcomes from around the world ( Table 1 and Table 2 ). The age of patients enrolled in these studies ranged from 24 to 100 years, with a greater proportion of men than women in most studies (proportion of women: 0% to 100%) ( Supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search yielded 171 studies, of which 38 studies met the eligibility criteria. The present analyses included a total of eighteen clinical trials including five RCTs, 7,8,12,13,15 thirteen matched-control studies, 11,16,2527,1724 and twenty case series or case reports 10,28,37–46,2936 containing 10,436 COVID-19 patient outcomes from around the world ( Table 1 and Table 2 ). The age of patients enrolled in these studies ranged from 24 to 100 years, with a greater proportion of men than women in most studies (proportion of women: 0% to 100%) ( Supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, when we aggregated mortality data from the thirteen matched-control studies, patients transfused with convalescent plasma exhibited a lower mortality rate compared to non-transfused patients (20% vs. 29% mortality; OR: 0.50, 95% CI: 0.37, 0.67, P < 0.001, I 2 = 61%) ( Table 1 and Figure 1 ). One study (Altuntas et al 27 ) represented the entire source of heterogeneity (Δ I 2 = 61%) among matched-control studies; however, this study was included in subsequent analyses as the OR for pooled matched-control data was similar when excluding the Altuntas et al 27 study (17% vs. 30% mortality; OR: 0.44, 95% CI: 0.38, 0.51, P < 0.001, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found in 30-day mortality rates (21.6% and 26.7%) [ 36 ]. There was a need for more mechanical ventilators in the CP group after 20 days in a study conducted in Turkey [ 37 ]. Our study showed that administering CP within the first five days in support of these data shortened hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, existem algumas questões que precisam ser claramente determinadas para otimizar o tratamento com plasma convalescente, como a eficácia e segurança do tratamento, o volume ideal de plasma, o número de transfusões, o intervalo entre as transfusões, o título ideal de anticorpo neutralizante, eficácia dos processos de inativação de patógenos, tempo e intervalos de doação ideais. Por isso, há necessidade de estudos prospectivos e randomizados em grande escala sobre o tratamento (ALTUNTAS et al, 2020).…”
Section: A Utilização Do Plasma Convalescente Para O Tratamento Da Covid -19unclassified
“…Ademais, após realizar uma análise de outros trabalhos, concluiu-se que a duração na unidade de terapia intensiva (UTI), a taxa de suporte de ventilação mecânica (VM) e suporte de vasopressor foram menores no grupo de pacientes que fizerem uso de plasma convalescente (PC) em comparação com o grupo controle. A taxa de letalidade foi de menor no grupo PC do que no grupo controle (ALTUNTAS et al, 2020).…”
Section: A Utilização Do Plasma Convalescente Para O Tratamento Da Covid -19unclassified